2011
DOI: 10.1021/np200036v
|View full text |Cite
|
Sign up to set email alerts
|

Archazolid A-15-O-β-d-glucopyranoside and iso-Archazolid B: Potent V-ATPase Inhibitory Polyketides from the Myxobacteria Cystobacter violaceus and Archangium gephyra

Abstract: CitationArchazolid A-15-O--D-glucopyranoside and iso-archazolid B: potent V-ATPase inhibitory polyketides from the myxobacteria Cystobacter violaceus and Archangium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…30). Recently, Menche and co-workers investigated both V-ATPase inhibition and the antiproliferative effect of archazolid derivatives and hypothesized that additional targets might be involved in their antitumour potential because of the much more pronounced antiproliferative activity, especially for derivatives with weaker V-ATPase inhibition 31 . Clear target identification may also enable the recognition and avoidance of unwanted side effects of future archazolid-derived chemotherapies and inform chemical scaffold modification for other indications.…”
Section: Resultsmentioning
confidence: 99%
“…30). Recently, Menche and co-workers investigated both V-ATPase inhibition and the antiproliferative effect of archazolid derivatives and hypothesized that additional targets might be involved in their antitumour potential because of the much more pronounced antiproliferative activity, especially for derivatives with weaker V-ATPase inhibition 31 . Clear target identification may also enable the recognition and avoidance of unwanted side effects of future archazolid-derived chemotherapies and inform chemical scaffold modification for other indications.…”
Section: Resultsmentioning
confidence: 99%
“…Archazolids potently inhibit V-ATPase activity (IC 50 : nanomolar range) exerting little or no effects on Na þ /K þ -ATPases and mitochondrial F-ATPases (8). To date, archazolid A, B, and F have been isolated from their natural producer and archazolid A and B have also been successfully chemically synthesized (9,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…(S233) that exhibit anticancer activity constitute watersoluble compounds and are unlikely to be previously described tubulysins. Horstmann et al (2011) reported inhibition of cervix and prostate cancer cell lines by secondary metabolites of Cystobacter sp. and Archangium sp.…”
Section: Discussionmentioning
confidence: 99%